Alien species affect the abundance and richness of native species in tropical forests: The role of adaptive strategies - Julissa Rojas‐Sandoval; James D. Ackerman; Humfredo Marcano‐Vega; Michael R. Willig (Ecosphere, 2022)
Abstract Understanding the role of alien species in forest communities, and how native and alien species interact to shape the composition and structure of contemporary forests, is of critical importance to invasion ecology and natural resource management. We used vegetation data collected over a 20‐year period in 341 permanent plots representing remnants of closed‐canopy forests and post‐agricultural secondary forests across Puerto Rico to compare changes in the composition and abundance of native and alien woody species in plots with and without aliens across different forest types and to assess whether aliens and natives show divergence or convergence regarding functional roles and ecological strategies. We also tested the applicability of Grime's CSR (competitive, stress‐tolerant, and ruderal strategies) theory to explain naturalization success. Species richness and abundance of natives are consistently lower in plots in which aliens are present compared with those without them. This negative association between aliens and natives has been consistent over the 20 years and across all forest types. Both native and total richness slightly increased over the 20 years, but the increase in native species richness was three times lower in plots with aliens relative to those without aliens. The CSR classification provided insight into the naturalization success of aliens. Corroborating the “join the locals” hypothesis, aliens use the same functional spaces as natives. The exception is in dry forests, where aliens and natives differ in the use of functional spaces, a result that corroborates the “try harder” hypothesis. Generally, aliens were better competitors compared with natives, and natives were more stress‐tolerant than aliens. Our combined results suggest that alien species may inhibit population growth or even drive local changes in native plant communities by transforming the assembly and dynamics of tropical forests. Ultimately, modifications linked to invasive species may have significant implications for local forests, affecting their regeneration and productivity. More definitive conclusions require additional plot censuses, and analyses of disturbance regimes and stand‐age structure to reveal the long‐term implications of alien species on regenerating tropical forests, including their vulnerability, resilience, and adaptive capacity to cope with various aspects of climate change.